Betamethasone valerate foam: a look at the clinical data. (March 2014) - Shemer, Avner; Sakka, Nicole; Tamarkin, Dov
Topical corticosteroids and especially betamethasone valerate (BMV) have been used topically to relieve many inflammatory skin conditions such as psoriasis and atopic dermatitis. The vehicle used to deliver topical drugs can influence the performance of these topical applications. BMV has traditionally been available in creams, ointments, lotions and sprays. In the early 2000s, a topical hydroethanolic BMV foam became commercially available. Subsequently, alcohol-free emulsion- and petrolatum-based foam formulations were also developed. This manuscript reviews the properties of BMV foams and clinical studies that have been conducted to assess their efficacy and safety as treatments for scalp and non-scalp psoriasis, as well as other dermatological inflammatory conditions.